Effect of denture quality on perioral muscle activity during speech - Carla Moreto Santos; Mathias Vitti; Maria da Glória Chiarelo Mattos; Marisa Semprini; Helena de Freitas Oliveira Paranhos; Jaime Eduardo Cecilio Hallak; Simone Cecilio Hallak Regalo (Universidade Estadual de Campinas, 2015)
This study aimed to evaluate the electromyographic activity of the orbicularis oris muscle in patients using clinically inadequate conventional dentures before and after the insertion of clinically acceptable new convencional denture. Six patients, using inadequate dentures, were asked to pronounce the syllables PAH, BAH, MAH, SAH, FAH, VAH, MEE and the word MISSISSIPI. During this activity, we analyzed the Electromyographic activity of the orbicularis oris muscle. This was done before and after changing the inadequate denture for a acceptable new denture. A K6-I EMG Light Channel Surface Electromyograph was used (Myo-tronics Co). Results were analyzed by repeated measures ANOVA, with 3 sources of variation (Syllables, Muscles, and Clinical Conditions). ANOVA revealed higher electromyographic readings in the mandibular fascicle of the orbicular oris muscle, as compared to those of the maxillary fascicle (F = 79.02; P<0.01). The comparison regarding clinical conditions indicated higher electromyographic values after insertion of acceptable new denture (F= 32.64; P<0.01). Clinical condition after the implantation of a new well-adapted complete denture revealed higher electromyographic activity levels than those measured with the use of maladapted complete dentures.